224k views
2 votes
Simplify by combining like terms: -4\left(2x-y\right)+y+5\left(x+y\right)−4(2−)++5(+) − 4 ( 2 x − y ) + y + 5 ( x + y ) ; use NO spaces when typing in your answers.

User Ryan Jeff
by
4.1k points

1 Answer

5 votes

Answer:

-3x+10y

Explanation:

Given the expression
-4\left(2x-y\right)+y+5\left(x+y\right), we are to simplify by combining the like terms. On simplification we have;


= -4\left(2x-y\right)+y+5\left(x+y\right)

Open the parenthesis:


= -4(2x)-4(-y)+y+5(x)+5(y)\\\\= -8x+4y+y+5x+5y

Collect the like terms:


= -8x+5x+4y+y+5y

Sum up the resulting expression


= -8x+5x+4y+y+5y\\= -3x+10y

Hence the required expression on simplification is -3x+10y

User Chris Burd
by
4.6k points